Distribution And Abundance Of Benthic Foraminifera Along The Intertidal Area Of Penang Island - Rijal, Syafiqah Syahirah Shah (2018)
The distribution and abundance of benthic foraminifera were studied in the intertidal areas of Penang Island. Five sites were selected namely Batu Feringghi, Jelutong, Pulau Betong, Teluk Aling and Teluk Kumbar. The samples of foraminifera were collected from three different intertidal zones i.e. low, middle and upper zones. A total of 375 sediment samples were collected bimonthly between May 2015 and January 2016. Environmental parameters (i.e. soil pH, salinity and temperature) were measured in-situ. Organic matter content was analyzed based on loss of ignition method (LOI) and particles size was determined based on Bale and Kenny (2005) method. A total of 9 genera of foraminifera were identified which include Ammonia, Elphidium, Quinqueloculina, Pseudorotalia, Bolivina, Nonionellina, Haynesina and Spiroloculina. Generally, the stress-tolerant taxa, Ammonia (64.11 %) and Elphidium (14.23%) dominated the assemblage at all sampling sites. Diversity indices showed that the intertidal area of Jelutong had the most diverse assemblage (H’ =1.61; D = 0.77) and Teluk Kumbar (H’= 0.43; D = 0.33) had the lowest foraminiferal assemblages. The cluster analysis classified the sites into two groups, of which each group was influenced by different environmental conditions. Group A (Batu Feringghi, Teluk Aling and Teluk Kumbar) was characterized as sandy (grained-size = 1 mm ~ 250 μm) with high pH (7.72), salinity (34.00 ppt) and temperature 33.5⁰C) (ANOVA, p<0.05). This group had a higher foraminiferal abundance but relatively low in diversity.